Multi-proxy reconstruction of Holocene and Late Glacial climate variability using precisely dated speleothems from the Herbstlabyrinth, central Germany - Mischel, Simon Andre (Johannes Gutenberg-Universität Mainz, 2016)
Speleothems grew in isolated places, in complete darkness and in harsh environments, in caves. Even so they are influenced by the climate of the surface surrounding the cave via percolating water from which they are precipitated. It is obvious that, beside the climate, the surface features, for example the type of vegetation, the stucture of the host rock and the soil properties alter the composition of the percolating water and thus, subsequently influences the drip water constituents. As a consequence, the geochemical composition of the precipitated speleothems are influenced by a variety of processes. These processes are of great interest when analysing speleothems, as they can vary spatially and temporally. The Herbstlabyrinth-Adventhöhle cave system provide an ideal place to study terrestrial past climate variability. First of all, the recent behavior of the drip water to seasonal or annual surface climate variability need to be investigated. This is achieved by a cave monitoring, where site specific influences can be discovered and important new insights in karst hydrology and speleothem science can be achieved. With this knowledge the interpretation of the proxy signals from the speleothems can be examined. To disentangle the individual influencing factors, sampling speleothems from different parts of the cave can help solving the variability on the spatial domain. To explain to which extent past climate variability is recorded by the speleothems, coeval specimen need to be analysed. In this thesis important progress could be made in terms of understanding the influences of climate pattern affecting the cave environment and the drip water and thus, the speleothems. The North Atlantic Oscillation has strong influence on the d18O values of the precipitation at the research area and subsequently, the drip water d18O values. A combination of research in the field and numeric modelling provide insight into the site specific behavior of the drip sites in the cave. As a consequence, the cave monitoring results ...